Showcasing the application of synchrotron‐based X‐ray computed tomography in host–pathogen interactions: The role of wheat rachilla and rachis nodes in Type‐II resistance to Fusarium graminearum. (23rd October 2018) - Brar, Gurcharn S.; Karunakaran, Chithra; Bond, Toby; Stobbs, Jarvis; Liu, Na; Hucl, Pierre J.; Kutcher, Hadley R.
Abstract: Fusarium head blight, caused primarily by Fusarium graminearum ( Fg ), is one of the most devastating diseases of wheat. Host resistance in wheat is classified into five types (Type‐I to Type‐V), and a majority of moderately resistant genotypes carry Type‐II resistance (resistance to pathogen spread in the rachis) alleles, mainly from the Chinese cultivar Sumai 3. Histopathological studies in the past failed to identify the key tissue in the spike conferring resistance to pathogen spread, and most of the studies used destructive techniques, potentially damaging the tissue(s) under study. In the present study, nondestructive synchrotron‐based phase contrast X‐ray imaging and computed tomography techniques were used to confirm the part of the wheat spike conferring Type‐II resistance to Fg spread, thus showcasing the application of synchrotron‐based techniques to image host–pathogen interactions. Seven wheat genotypes of moderate resistance to Fusarium head blight were studied for changes in the void space volume fraction and grayscale/voxel intensity following Fg inoculation. Cell‐wall biopolymeric compounds were quantified using Fourier‐transform midinfrared spectroscopy for all genotype‐treatment combinations. The study revealed that the rachilla and rachis nodes together are structurally important in conferring Type‐II resistance. The structural reinforcement was not necessarily observed from lignin deposition but rather from an unknown mechanism. Abstract : Our manuscript reports the successful application of synchrotron‐based X‐ray imaging methods to study the wheat– Fusarium interaction, thus providing an understanding of the structural role of the spike in Type‐II resistance, which is defined as resistance to pathogen spread. The major merit associated with our manuscript is in terms of technical advancement because the methods and approaches/algorithms described can be applied to the study of plant biology, such as host–pathogen interactions or developmental changes in plant tissues. Our study is one of very few to study host–pathogen interactions and the first to be applied to the wheat– Fusarium interaction. It demonstrated the use of X‐ray imaging techniques for direct observation of the host–pathogen interaction without destructive sampling.